Students Higher Order Thinking Skills: Analyze, Evaluate, Create Green Consumerism Solution in Environmental Learning - Ichsan, Ilmi Zajuli; Sigit, Diana Vivanti; Miarsyah, Mieke (Universitas Malikussaleh, 2019)
Environmental learning in schools should be based on Higher Order Thinking Skills (HOTS) and based on environmental problems, one of which is Green Consumerism (GC). The problem is the absence of student HOTS profiles based on GC. The purpose of this study was to measure students HOTS based on GC concepts and present them descriptively in the form of profiles. The study was conducted in November-December 2018 at State Junior High School 1 in South Tambun, Bekasi, West Java, Indonesia. The research method used is descriptive research. The sample used was 128 students in grade 8th, consisting of 42 male students and 86 female students. The results showed that GC-based HOTS scores were still relatively low. Students overall got an average score of 31.55. The aspect with the highest score was obtained in the analyze (C4) aspect with a score of 3.81, while the aspect with the lowest score was on the create aspect (C6) with a score of 2.57. This is because the information about GC is still not obtained by many students. The conclusion is that students' HOTS scores are low and need to be improved.